COMMON MISTAKES IN MAKING A PRESENTATION - Madina Gafforova; Mahbuba Holmatova (Web of Journals Publishing, 2025)
Presentations are an essential part of academic, professional, and educational settings. However, students encounter common mistakes that undermine the effectiveness of their delivery. This article explores frequent mistakes in presentation and guides students in developing engaging and impactful presentations.
Keywords: Presentation, conference, seminar, audience, structure, visual.